Encyclopedia of global industries [2007] (Gale virtual reference library, 2007)
Chronicles the history, development and current status of the world's most lucrative and high profile industries. Each entry covers size and economic/social impact of the industry; its organization and structure; its history and development; major countries and companies involved (including rankings); size and nature of the work force; and research.